Expression of cytokine- and chemokine-related genes in peripheral blood mononuclear cells from lupus patients by cDNA array - Rus, Violeta (Clinical immunology (Orlando, Fla.), 2002)
Systemic lupus erythematosus (SLE) is characterized by diverse and complex immune abnormalities. In an effort to begin to characterize the full complexity of immune abnormalities, the expression pattern of 375 potentially relevant genes was analyzed using peripheral blood mononuclear cells (PBMC) from 21 SLE patients and 12 controls by cDNA arrays. When mean gene expression for patients was compared to controls, 50 genes were identified that exhibited more than 2.5-fold difference in expression level. By the Mann-Whitney U test, 20 genes were significantly different (P < 0.05) between patients and controls. Most of these genes have not been previously associated with SLE and belong to a variety of families such as TNF/death receptor, IL-1 cytokine family, and IL-8 and its receptors. Hierarchical clustering of samples and differentially expressed genes revealed that with few exceptions, patients clustered separately from controls. These results highlight the potential use of the microarray data in identifying genes associated with SLE, which could become candidate molecular markers or future therapeutic targets